Optimal Investment Decision of Distribution Network With Investment Ability and Project Correlation Constraints - Yang, Jianping; Xiang, Yue; Wang, Zeqi; Dai, Jiakun; Wang, Yanliang (Frontiers in Energy Research, 2021)
Power grid enterprises are faced with a serious mismatch between limited investment capacity and numerous investment projects. How to accurately match the weak links with investment projects according to the power system diagnosis is the key to improve investment accuracy. On the basis of an investment-oriented label, a project portfolio optimization framework with coherent diagnosis–evaluation–optimization is proposed in this study. First, a two-layer index system for investment benefit evaluation is established, which considers unit investment efficiency and macroinvestment benefit. Second, by weighing the diagnosis results of power grid and the biased investment environment, the benefit evaluation of the project is implemented as the basis of project portfolio optimization. To meet different investment demands, two combination optimization models of maximizing investment benefit and minimizing investment cost are established considering the coupling benefit relationship and time series relationship between projects. Finally, a case study is conducted for a regional distribution network. The proposed framework has been proven to be able to effectively cope with different investment needs and realize the dynamic adjustment of the scheme in the whole investment cycle.